Patient and Provider Perspectives on a Mind–Body Program for Grieving Older Adults. (June 2018) - Bui, Eric; Chad-Friedman, Emma; Wieman, Sarah; Grasfield, Rachel H.; Rolfe, Allison; Dong, Melissa; Park, Elyse R.; Denninger, John W.
Background: Spousal bereavement in older age is a major stressor associated with an increase in both mental and physical problems. The Stress Management and Resiliency Training: Relaxation Response Resiliency Program (SMART-3RP) is an 8-week multimodal mind–body program that targets stress and has been found efficacious in decreasing the mental and physical manifestations of stress in varied populations. This qualitative study sought to investigate the relevance, credibility, and feasibility of the SMART-3RP in the community. Methods: Focus groups were conducted among both older widowed adults and providers who support them in the community (eg, chaplains, hospice bereavement coordinators). Transcripts were coded independently by coders trained in qualitative research. Codebooks were created based on both general themes and detailed subthemes present in the transcripts. Results: Findings from 4 focus groups revealed a general convergence between the needs of recently widowed older adults reported by widow(er)s and community providers alike and needs identified in the literature. Several components of the SMART-3RP target many of these needs (eg, social support, stress awareness, coping skills), making both community providers and widow(er)s report that the SMART-3RP is logical (89%) and would be helpful (100%) and successful in reducing symptoms (78%). Additionally, all widow(er)s reported a willingness to participate (100%). Feedback from the focus groups was used to adapt the SMART-3RP to improve its relevance to grief-related stress. Conclusions: Our findings suggest that the SMART-3RP may be helpful in decreasing somatic and psychological distress in older adults who have lost a spouse.